Getting started in a financially secure retirement - Hebeler, Henry. K. (John Wiley & Sons, 2007)
If you want to make the most of your retirement years, you have to seriously think about the retirement lifestyle you want and the path that will get you there. In order to do this, you need reliable retirement information that will allow you to properly chart your course. Nobody knows this better than author Henry Hebeler, who retired from the corporate world more than fifteen years ago--and quickly discovered that much of the retirement planning advice available wasn't helping people accomplish their goals.